Phase transition of intermetallic TbPt at high temperature and high pressure. (12th March 2018) - Qin, Fei; Wu, Xiang; Yang, Ke; Qin, Shan
Abstract: Here we present synchrotron-based x-ray diffraction experiments combined with diamond anvil cell and laser heating techniques on the intermetallic rare earth compound TbPt ( Pnma and Z = 4) up to 32.5 GPa and 1800 K. The lattice parameters of TbPt exhibit continuous compression behavior up to 18.2 GPa without any evidence of phase transformation. Pressure–volume data were fitted to a third-order Birch–Murnaghan equation of state with V 0 = 175.5(2) Å 3, K T 0 = 110(5) GPa and K T 0 ′ = 3.8(7). TbPt exhibits anisotropic compression with β a > β b > β c and the ratio of axial compressibility is 2.50:1.26:1.00. A new monoclinic phase of TbPt assigned to the Pc or P 2/ c space group was observed at 32.5 GPa after laser heating at 1800 K. This new phase is stable at high pressure and presented a quenchable property on decompression to ambient conditions. The pressure–volume relationship is well described by the second-order Birch–Murnaghan equation of state, which yields V 0 = 672(4) Å 3, K T 0 = 123(6) GPa, which is about 14% more compressible than the orthorhombic TbPt. Our results provide more information on the structure and elastic property view, and thus a better understanding of the physical properties related to magnetic structure in some intermetallic rare earth alloys.